Spin-phonon induced magnetic order in magnetized Spin Ice systems - Gómez Albarracín, Flavia Alejandra (2014)
We study the behavior of spin ice pyrochlore systems above the well known [111] 1/3 plateau, under slight deviations of the direction of the external field. We model the relevant degrees of freedom by Ising spins on the kagome lattice. We propose the inclusion of lattice deformations, which imply phononic degrees of freedom in the adiabatic limit. We use analytical calculations to estimate how these new degrees of freedom affect the short and long range spin interactions in the presence of an external magnetic field. We then obtain the magnetization curves, explore the phases and the ground states of this system in the presence of magnetic field by Monte Carlo simulations. We discuss comparisons with experimental results.